Cambodia for sale : everyday privatization in education and beyond - Brehm, Will (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Cambodia for Sale: Everyday Privatization in Education and Beyond details a post-conflict society that socializes children into a world of private rather than public goods. Despite the government's best efforts since the 1990s to re-constitute a functioning system of public services, life remains organized around buying and selling virtually everything, from humanitarian aid to schooling and from religious good deeds to irrigation. Through an ethnography of one village, Cambodia for Sale argues that efforts to rebuild Cambodia after decades of conflict have resulted in various forms of everyday privatization. Although this is most notable in the education system, these practices of privatization can be found in multiple institutions that constitute social life, from the Buddhist pagoda to local government. The various efforts of international development are as much at fault for this reality as are the legacies of the genocidal Khmer Rouge regime. This argument unfolds through the life stories of six residents of the Preah Go village, who collectively depict everyday life through overlapping village institutions, systems, and histories. This is an insightful and valuable reference for scholars interested in educational development, Southeast Asian studies and comparative education"--
OCLC-licensed vendor bibliographic record.
Keywords: Privatization -- Cambodia; Cambodia -- Economic conditions -- 20th century; Cambodia -- Social conditions -- 20th century; EDUCATION / General